Phase stabilisation, thermal expansion and ionic conductivity of high content rare earth oxide (Lu2O3, Y2O3 and Gd2O3) stabilised cubic hafnia. Issue 9 (August 2023) - Sévin, L.; Audouard, L.; Razafindramanana, V.; Mauvy, F.; Galzin, L.; Justin, J.-F.; Bertrand, P.; Langlade, C.; Garcia, M.; Julian-Jankowiak, A.
Abstract: For satellite propulsion, new material are developed to sustain harsh thermal and environmental conditions in the combustion chambers induced by the development of new "green" propellants less toxic than currently used hydrazine. In the present study, hafnia-based materials with different amounts and natures of stabilisers (Lu2 O3, Y2 O3 and Gd2 O3 ) have been chosen for the ceramic part of the system. Microstructures, Thermal Expansion Coefficients (373–1673 K) and ionic conductivities (600–1273 K) of synthesised fully stabilised fluorite phases have been investigated. Lattice parameters have been determined and an abacus has been proposed as a function of the amount of RE2 O3 and the ionic radius of the Rare Earth cation (RE 3+ ). Moreover, it has been observed a TECs decrease from 14 to 40 mol% of RE2 O3 and few changes in the ionic conductivity above 33 mol% of RE2 O3 . Finally, addition of Lu2 O3 allows to reach the lowest TEC and ionic conductivity.